SAINS UNTUK ANAK: HAKIKAT PEMBELAJARAN SAINS UNTUK SEKOLAH DASAR - Barlia, Lily (Jurnal Cakrawala Pendidikan, 2016)
Up to now, science educators are still confronted with· students who are unmotivated to learn science. They are generally unwilling to learn science for conceptualunderstanding. They rely on less appropriate learning strategies such as distorting scientific knowledge to fit their existing knowledge, mindlessly answering questions, copying answers from others, or not completing their work. They also spend time and effort focusing· on less important learning.outcomes, .such as memorizing science vocabulary or factual.information, rather than achieving scientific understanding. On the other hand, it is believed that motivation is an important factor in the process of student learning for· conceptual understanding. This is a· sufficient reason for science educators to consider the .importance of science teaching strategies to increase students' motivation in the process of student learning. In addition, they need to develop, refine, and reform the process of teaching and learning science itself. There are at least· three strategies they can use to increase students' motivation to learn science for conceptual understanding: 1) using immediate students' environment as learning· sources; 2) selecting instruction materials related to students' existing knowledge; 3) relating instruction materials to students' daily life needs. Finally, science educators have to be aware of the importance of affective aspects and students' motivation to learn. They have to decide how to conduct instruction that can help students learn in meaningful ways, including understanding of why, where, and what for students learn science